Rickettsia spp., Ehrlichia sp. and Candidatus Midichloria sp. associated to ticks from a protected urban area in Buenos Aires City (Argentina) - Cicuttin, Gabriel L.; De Salvo, María Nazarena; Venzal, José Manuel; Nava, Santiago (Springer, 2022)
The aim of this study was to determine the infection with Rickettsiales in ticks and birds from the main protected urban area of Buenos Aires City (Argentina). One Amblyomma aureolatum (0.2%) and one Ixodes auritulus (0.1%) were positive by PCR targeting Rickettsia 23S-5S rRNA intergenic spacer. Phylogenetic analysis shows to findings in A. aureolatum are closely to Rickettsia bellii and for I. auritulus are related to ‘Candidatus Rickettsia mendelii’. One I. auritulus (0.1%) and three A. aureolatum (0.6%) were positive by PCR for a fragment of the 16S rRNA gene of the Anaplasmataceae family. The sequences obtained from A. aureolatum were phylogenetically related to Midichloriaceae endosymbionts. The sequence from I. auritulus s.l. had 100% identity with Ehrlichia sp. Magellanica from Chile and two genotypes of Ehrlichia sp. from Uruguay. The results of our study show that Rickettsia and Ehrlichia are present in ticks in the main protected urban area of Buenos Aires City.